Colton storm warning - Davis, Justine (Coltons of Kansas, 2020)
"When security expert Ty Colton is assigned to protect a young heiress, he doesn't know what to expect. Turns out that Ashley Hart is a committed philanthropist with a real target on her back. She's earned a very dangerous enemy, and Ty's sense of duty takes over. As a storm bears down hard, will their growing feelings prove a fatal distraction--or the bond that saves them both?" -- Amazon.com.